Oestradiol and sex hormone-binding globulin in premenopausal and post-menopausal meat-eaters, vegetarians and vegans. - Thomas, H; Davey, G; Key, T (1999)
Endogenous oestradiol is strongly associated with breast cancer risk but its determinants are poorly understood. To test the hypothesis that vegetarians have lower plasma oestradiol and higher sex hormone-binding globulin (SHBG) than meat-eaters we assayed samples from 640 premenopausal women (153 meat-eaters, 382 vegetarians, 105 vegans) and 457 post-menopausal women (223 meat-eaters, 196 vegetarians, 38 vegans). Vegetarians and vegans had lower mean body mass indices (BMI) and lower plasma cholesterol concentrations than meat-eaters, but there were no statistically significant differences between meat-eaters, vegetarians and vegans in pre- or post-menopausal plasma concentrations of oestradiol or SHBG. Before adjusting for BMI there were small differences in the direction expected, with the vegetarians and vegans having higher SHBG and lower oestradiol (more noticeable amongst post-menopausal women) than the meat-eaters. These small differences were essentially eliminated by adjusting for BMI. Thus this study implies that the relatively low BMI of vegetarians and vegans does cause small changes in SHBG and in post-menopausal oestradiol, but that the composition of vegetarian diets may not have any additional effects on these hormones.